Symptom Association for Gastroesophageal Reflux Disease by pH Monitoring After Peroral Endoscopic Myotomy. (25th August 2022) - DeWitt, John M.; Kessler, William R.; Wo, John M.; Stainko, Sarah; Perkins, Anthony; Dickason, Destenee; Al-Haddad, Mohammad A.; Siwiec, Robert
Abstract : INTRODUCTION: There are limited data correlating symptoms with reflux episodes during pH studies after peroral endoscopic myotomy. METHODS: Consecutive patients who underwent POEM followed up ≥6 months later by 48-hour ambulatory wireless pH testing off antisecretory therapy were identified. Reflux symptom association was defined as symptom association probability >95%. RESULTS: The most frequent symptoms of heartburn (47.2%), cough (45.1%), and chest pain (39.6%) were associated with a positive reflux symptom association (symptom association probability >95%) in 20.9%, 17.1%, and 19.4%, respectively. DISCUSSION: There is poor correlation between reported symptoms and esophageal acid exposure during pH testing after POEM.